Electrostatic evaluation of a unipolar diffusion and field charger of aerosol particles by a corona discharge - Intra P. (2014)
This article presents a unipolar diffusion and field charger by corona discharge is presented and electrostatically evaluated for charging aerosol particles. The electrostatic characteristics of the charger were investigated with an electrometer by measuring the ion number concentrations corresponding to the discharge and charging currents. The discharge and charging currents, and ion number concentration in the discharge and charging zones of the charger, increased with corona voltage. The magnitudes of the ion number concentration for positive and negative coronas in the discharge zone ranged from 1.34 × 1013 to 1.84 × 1015 ions/m3 and 7.34 × 1013 to 2.64 × 1015 ions/m3, respectively. For the charging zone, the ion number concentrations for positive and negative coronas ranged from 2.95 × 1013 to 1.52 × 1014 ions/m3 and 2.06 × 1013 to 1.47 × 1014 ions/m3, respectively. To predict the behavior of the electric field strength and lines in the discharge and charging zones of the charger, the electric field strength and distribution of the charger in the discharge and charging zones were calculated by a commercial computational fluid dynamics software package. Numerical calculation results of electric field distribution and lines through the inner electrode showed good agreement with experimental results. Also, the mean charge per particle for particle diameters were in the range of 0.01 to 50 m for various operating conditions of the charger was theoretically evaluated. For both diffusion and field charging, lower aerosol flow rate and higher corona voltage resulted in an increase in the mean charge per particle within the charger. This simple charger proved to be particularly useful in diffusion and field charging of aerosol particles in particulate matter detector instruments for measuring PM10 and PM2.5 concentration. © 2013 Copyright Taylor and Francis Group, LLC. © 2013 Taylor & Francis Group, LLC.